Hanta Ua Pua Tradition: Integration of Islam and local wisdom of the Mbojo Tribe (Bima-Dompu) - Nur, Muhammad; Qalbi, Nur Latifatul; Hasaniyah, Nur (Maliki Interdisciplinary Journal, 2024)
Hanta Ua Pua is one of the preserved and practiced traditions among the Bima-Dompu community. It represents a cultural aspect that has become part of Islam, particularly in the Bima-Dompu society. This research aims to uncover how Hanta Ua Pua is believed and functions as a religious belief and activity in the community, which, from a religious perspective, is not entirely derived from religious teachings. The research utilizes content analysis methodology. Islam holds a concept of universalism capable of integrating and assimilating into various civilizations and cultures. It can coalesce and be embraced by diverse nations and civilizations. The Bima-Dompu community regards Hanta Ua Pua as an activity associated with reinforcing faith and devotion to religion due to its inherent religious values that must be upheld. This is evident from its three objectives: first, honoring the birth of Prophet Muhammad SAW; second, recalling the history of the spread of Islam in the land of Bima and the establishment of the Bima Sultanate; third, paying homage to the contributions of the ulamas, the Melayu leaders, and all families involved in disseminating Islam in Bima. Considering these three objectives, it can be concluded that Hanta Ua Pua is deeply steeped in Islamic values and reinforces belief in Islamic principles, making it a mandatory activity for the Bima-Dompu community.